Investigations of thermal behavior, flow structure, and performance in a circular tube heat exchanger fitted with diamond-shaped orifice (DSO): a CFD assessment - Boonloi, Amnart; Jedsadaratanachai, Withada (Frontiers in Mechanical Engineering, 2025)
This study numerically investigates the enhancement of heat exchanger performance using a passive technique based on vortex generation. The proposed enhancement device, termed a diamond-shaped orifice (DSO), is a modified configuration that combines a conventional orifice plate with a conical ring. The DSO is inserted into a circular tube to modify the flow structure and induce strong vortices, thereby promoting convective heat transfer and improving the overall thermal performance. The effects of key geometric parameters, including the attack angle (α = 20°, 30°, and 45°), flow blockage ratio (FBR = 0.05–0.30), and pitch ratio (PRT = 1–2), are systematically examined under turbulent airflow conditions with Reynolds numbers ranging from 3,000 to 20,000. The results reveal that incorporating the DSO generates intense swirling flow, which effectively disrupts the thermal boundary layer and enhances the convective heat transfer coefficient. The maximum Nusselt number improvement reached 7.16 times that of a plain tube, while the highest thermal enhancement factor (TEF) attained was 1.77, indicating a substantial improvement in heat exchanger performance without additional active energy input.